Implementasi Budaya Keselamatan Pasien oleh Perawat di Rumah Sakit Ibnu Sina Makassar - Syam, Nur Syarianingsih (Universitas Ahmad Dahlan, 2017)
Background: The incidence of medication errors to patients on hospital have been reported in some cases. Indonesia was launched